(untitled) (Bulletin KNOB, 1996)
The ’Dutch school’ of fortification theory influenced Portuguese military architecture in the seventeenth century in two ways. On the one hand, shortly after the Restauraçao (1640), two engineers, Cosmander and Gillot, came to Portugal from The Netherlands and fortified several Portuguese cities, thus introducing the Dutch tradition, which greatly influenced the practical execution of Portuguese fortification architecture for a long time. On the other hand, there was also great influence from The Netherlands through treatises on fortification architecture. These treatises were often sent directly to Portugal from the Dutch Republic or Flanders (where Portuguese engineers served in the Spanish armies). In particular, they were studied at the Aula de Esfera in the Collégio de Santo Antão in Lisbon, a Jesuit college. In 1647 the Aula de Fortificaçao e Arquitectura Militar was founded, an institute exclusively aimed at the teaching of fortification architects. This institute was under the inspiring leadership of Luís Serrao Pimentel, the most important fortification architect in Portugal in the seventeenth century. Pimentel made a very thorough study of the Dutch treatises and used them as a source of inspiration when he compiled his own Methodo Lusitanico (Portuguese Method), a book which was not published until after his death. The manuscripts written by Pimentel also show his preference for the Dutch school. The first, most important and probably most voluminous handwriting, the Hercotectonica, was used as a Standard work by his students, the later fortification architects in the war against Spain (1640-1667). In the Hercotectonica Pimentel worked with the Rhineland foot as the unit of measure. The huge influence Pimentel had on Portuguese fortification architecture in the seventeenth century indirectly reflects the enormous effect of Dutch military architecture at that time.